2018
DOI: 10.30684/etj.36.5a.1
|View full text |Cite
|
Sign up to set email alerts
|

On the Performance of a Microstrip Antenna Based UC-PBG Structures for UHF RFID Readers

Abstract: Microstrip antennas suffer from low gain bandwidth product due to surface wave effects and aperture diffractions that limit their use for longrange communications. On top of that, the difficulty of achieving a pure circularly polarized radiation with high gain due to the feeding structure effects. This paper is subjected to design a gain enhanced circularly polarized patch antenna using Uniplanar Compact-Photonic Band Gap (UC-PBG) structu.res for UHF RFID applications. The patch is structured as truncated corn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Thus, four PIN diodes are connected between the L‐shaped reflector and the MLC inclusion to control the matching bandwidth and the radiation patterns within 16 scenarios. We found that the proposed antenna shows excellent and stable variation in the radiation patterns direction as well as the bandwidth, because there is no direct connection between the PIN diodes and the monopole structure that isolated the RF source from the DC source completely 8 . In Table 4, the proposed antenna is tested numerically, and the performance of the antenna in terms of frequency resonance, S 11 , gain, and bandwidth (B.W) is summarized.…”
Section: Systematic Study and Design Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, four PIN diodes are connected between the L‐shaped reflector and the MLC inclusion to control the matching bandwidth and the radiation patterns within 16 scenarios. We found that the proposed antenna shows excellent and stable variation in the radiation patterns direction as well as the bandwidth, because there is no direct connection between the PIN diodes and the monopole structure that isolated the RF source from the DC source completely 8 . In Table 4, the proposed antenna is tested numerically, and the performance of the antenna in terms of frequency resonance, S 11 , gain, and bandwidth (B.W) is summarized.…”
Section: Systematic Study and Design Methodologymentioning
confidence: 99%
“…We found that the proposed antenna shows excellent and stable variation in the radiation patterns direction as well as the bandwidth, because there is no direct connection between the PIN diodes and the monopole structure that isolated the RF source from the DC source completely. 8 In Table 4, the proposed antenna is tested numerically, and the performance of the antenna in terms of frequency resonance, S 11 , gain, and bandwidth (B.W) is summarized. It is found that the proposed antenna shows maximum gain, about 4.72 dB, at 0001 case, in which D 1 , D 2 , and D 3 are OFF and D 4 is ON.…”
Section: Reconfiguration Scenariosmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have worked in this field and have used these structures as high impedance structures [19], metasurfaces [20], polarization-dependent EBG surfaces [21], etc. When implemented on antenna's ground plane, EBG structures showed an improved performance [22][23][24]. The attractive features of EBG structures has made these structures be used in broad area of applications in the antenna field.…”
mentioning
confidence: 99%